Raccontare il mondo, descrivere la natura L'opera di Alexander von Humboldt tra letteratura e scienza - Serra, Valentina; Tanca, Marcello (RESOCONTI, 2023)
Described by his contemporaries as one of the most celebrated men of his time, Alexander von Humboldt (1769-1859) was one of the most admired figures of the 19th century. A younger brother of Wilhelm, Alexander was both and at the same time a botanist, naturalist, explorer and geographer. In 1799 he embarked with Aimé Jacques Alexandre Bonpland (1773-1858) on a voyage that took them first to Tenerife, then to Venezuela, Colombia, Cuba, Ecuador, Peru and Mexico. The fruit of this and other adventurous voyages is a substantial literary and scholarly output, which in this volume is investigated together with the many facets of the figure of Humboldt and the many influences of his work and thought in the fields of history, geography, literature and linguistics.